: Telur, kayu kesambi, waktu pe SMOKING OF EGGS WITH DIFFERENT LENGTH OF TIME AND THE EFFECT OF SMOKE (Schleihera Oleosa Merr) ON PHYSICOCHEMICAL AND ORGANOLEPTICS OF CHICKEN EGGS: SMOKING OF EGSS WITH DIFFERENT TIME LENGTH AND THE EFFECT OF SMOKE KESAMBI (SCHLEIHERA OLEOSA MERR) ON PHYSICOCHEMICAL AND ORGANOLEPTICS OF CHICKEN EGGS (Jurnal Peternakan Nusantara, 2022)
This study aims to determine the best smoking time in the process of processing smoked salted eggs by analyzing the water content, pH, total phenol and organoleptic in smoked salted eggs. This study used a completely randomized design, namely smoking eggs with different lengths of time having four treatment levels, namely P1 = 130 minutes, P2 = 150 minutes, P3 = 170 minutes, P4 = 190 minutes. The required smoking time is 20 sample units. The variables measured were water content, pH, total phenol and organoleptic including color, taste, texture and preference. Parameter testing includes water content, pH first tested for normality using the Shapiro-Wilk test. If the data distribution is normal, it is continued with Duncan's Multiple Region test. Total phenol was tested descriptively and organoleptic testing (color, taste, texture and preference) using the Kruskal-Walis Non-parametric test and continued, the Man Witney significant difference test. The results of this study indicate that different lengths of smoking time can have a significant effect (<0.05) on water content, pH and organoleptic. The smoking time of 190 minutes can reduce water content, pH but increase panelists' acceptance of organoleptic (color, taste, texture and preference) in eggs and the presence of antioxidant activity.